Guggenheim expansion - Nagy, Andrea R.; Barton-Sweeney, Alexandra (London : SAGE Publications Ltd, 2017)
Traditionally museums have been institutions closely tied to a great city. The Metropolitan Museum of Art is part of New York; the Louvre is a monument of Paris; the Hermitage is a landmark of St. Petersburg. Like a famous university or library or hospital, a museum was thought to be one of a kind, no more reproducible than the great works of art that it houses.But during the 1990s, this concept of the museum began to change, as the scale of operations grew in every way. Traveling exhibitions grew to become money-making blockbusters attracting large crowds. Art works themselves became larger, which required larger exhibition space. And as the economy expanded, increasing donations allowed museums to buy new art and to build additional wings to house their collections. As The Wall Street Journal put it in a 1999 article, "It's party time these days in the normally staid and sober museum world."
Originally published: Nagy, A. R., & Barton-Sweeney, A. (2008). Guggenheim expansion. 08-026. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol09.cases.som.yale.edu/guggenheim-expansion.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Solomon R. Guggenheim Museum; Museums -- Social aspects; Museum attendance; Art, Modern -- 20th century